Surgical Treatment of Patients with Damage to the Ligaments Holding the Long Head of the Biceps (Pulley Lesion) in Combination with Contracture of the Shoulder Joint - Bohdan, S.V.; Yuriichuk, L.M.; Lieskov, V.H. (TERRA ORTHOPAEDICA, 2023)
Background. Damage to the ligaments holding the long head of the biceps, or Pulley Lesion injuries, are often accompanied by contracture of the shoulder joint. Objective. The objective of the study was to compare the treatment outcomes of patients with Pulley Lesion injuries and secondary adhesive capsulitis. Material and Methods. The study included 82 patients with contracture of the shoulder joint and damage to the ligaments holding the long head of the biceps. The patients were divided into 2 groups depending on the extent of surgical intervention: group 1 underwent subpectoral tenodesis and selective capsulotomy of the shoulder joint; group 2 underwent subpectoral tenodesis without selective capsulotomy of the shoulder joint. The function of the shoulder joint was assessed using the Constant Shoulder Score and VAS scales before surgery, at 3 and 6 months after the surgery. Results. At 3 months follow-up, the average functional result according to the Constant Shoulder Score was somewhat worse in group 2 (14.5±5.2 points) than in group 1 (8.5±6.4 points), p = 0.031. At 6 months follow-up, the average functional result according to the Constant Shoulder Score was 5.1±5.6 points in group 1 and 10.1±4.1 points in group 2 (p = 0.024). At 3 months follow-up, the average VAS score was worse in group 2 than in group 1 and reached 2.81±0.7 points. At 6 months follow-up, the average VAS score in group 2 was also worse than in group 1 (p = 0.051). Conclusions. Performing selective capsulotomy and subpectoral tenodesis in patients with secondary adhesive capsulitis and damage to the ligaments holding the long head of the biceps (Pulley Lesion injuries) allows us to achieve better functional results both according to the Constant Shoulder Score and the VAS scale at 3 and 6 months after the surgery.